A catalyst for selective hydrogenation of alkynes and preparation method thereof

By using the organic cage support structure of Pd and Ag in the alkyne selection hydrogenation catalyst, combined with the geometry and electron effects of silver, the problem of catalysts being prone to green oil and coke is solved, which improves selectivity and service life, and reduces the amount of by-product generation.

CN117463325BActive Publication Date: 2025-04-25PETROCHINA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210847575.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-19
Publication Date
2025-04-25
Estimated Expiration
2042-07-19

AI Technical Summary

Technical Problem

The existing alkyne selective hydrogenation catalysts are prone to produce green oil and coke during use, resulting in a decrease in activity and shortened service life, and at the same time, the selectivity is not ideal.

Method used

A selective hydrogenation catalyst containing Pd and Ag is used, and the active components of the catalyst are supported by an organic cage, which is supported in the organic cage, and Ag is located in the middle or bottom of the active center of Pd, thereby improving the selectivity of the catalyst through the geometry and electron effects of silver.

Benefits of technology

It effectively reduces the formation of green oil and the coking of the catalyst, extends the service life of the catalyst, improves the selectivity of the catalyst, and reduces the generation of four carbon by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117463325B_ABST
    Figure CN117463325B_ABST
Patent Text Reader

Abstract

The present invention provides an alkyne selective hydrogenation catalyst and a preparation method thereof. The active components of the catalyst contain at least Pd and Ag, and based on the mass of the carrier as 100%, the content of Pd is 0.045-0.075%, and the content of Ag is 0.06-0.12%; the catalyst contains an organic cage, the organic cage is located on the outer surface of the catalyst, the size of the organic cage is 2.7-3.6nm, the Pd is loaded in the organic cage, and the Ag is located in the middle or bottom of the Pd active center. The catalyst of the present invention is applied to the selective hydrogenation process of carbon distillation, the yield of butene can be reduced to less than 1 / 2 of that of the traditional catalyst, and the generation amount of oxygen-containing compounds such as aldehydes is also greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an alkyne selective hydrogenation catalyst and a preparation method thereof, belonging to the technical field of catalyst preparation. Background Art

[0002] Ethylene obtained by steam cracking of petroleum hydrocarbons (such as ethane, naphtha, diesel, hydrogenated tail oil, etc.) contains 0.2%-2.5% acetylene by mass. When used for polymerization, the acetylene in ethylene will reduce the activity of the polymerization catalyst and affect the physical properties of the polymer, so it must be removed. At present, the industry generally adopts the method of selective hydrogenation to remove acetylene from ethylene, and the catalysts used are mainly precious metal catalysts such as Pd, Pt, and Au. In order to ensure that the ethylene generated by acetylene hydrogenation and the original ethylene in the raw material do not continue to hydrogenate to generate ethane, resulting in ethylene loss, it is necessary to ensure that the catalyst has a high hydrogenation selectivity in order to obtain better economic benefits.

[0003] The post-hydrogenation of C2 is based on the content of acetylene, and the required hydrogen is calculated and added to the hydrogenation material. The molar ratio of hydrogen to acetylene is generally not more than 2. It is precisely because of the small amount of hydrogen that the hydrogenation dimerization reaction of acetylene occurs easily to generate C4 fractions, which are further polymerized to generate oligomers with a wider molecular weight, commonly known as "green oil". Green oil is adsorbed on the catalyst surface and further forms coke, blocking the catalyst pores, so that the reactants cannot diffuse to the surface of the catalyst active center, thereby causing the catalyst activity to decrease.

[0004] Noble metal catalysts have high activity, but they are prone to generate green oil during use, which causes the catalyst to coke and deactivate, affecting the stability and service life of the catalyst. CN200810119385.8 discloses a non-noble metal supported selective hydrogenation catalyst and its preparation method and application, including a carrier and a main active component and an auxiliary active component supported on the carrier, wherein the main active component is Ni, the auxiliary active component is selected from at least one of Mo, La, Ag, Bi, Cu, Nd, Cs, Ce, Zn and Zr, the main active component and the auxiliary active component are both in amorphous form, with an average particle size of <10nm, the carrier is a non-oxidizing porous material; and the catalyst is prepared by microemulsion method.

[0005] CN200810114744.0 discloses a catalyst for selective hydrogenation of unsaturated hydrocarbons and a preparation method thereof. The catalyst uses alumina as a carrier and palladium as an active component, and adds rare earth and alkaline earth metals and fluorine to improve the catalyst's resistance to impurities and coking, but its catalyst selectivity is not ideal.

[0006] The catalysts prepared by the above methods all use catalysts with single pore size distribution. In the fixed bed reaction process, they are affected by internal diffusion and the selectivity of the catalyst is poor. The carrier with bimodal pore distribution can reduce the influence of internal diffusion while ensuring the high activity of the catalyst, and improve the selectivity of the catalyst. CN101433842A discloses a hydrogenation catalyst, which is characterized in that the catalyst has a bimodal pore distribution, the most probable radius of the small pore part is 2-50nm, and the most probable radius of the large pore part is 100-500nm. Since the catalyst has a bimodal pore distribution, it has good hydrogenation activity and good selectivity, and the ethylene increment is large.

[0007] In the carbon dihydrogenation reaction, the generation of green oil and the coking of the catalyst are important factors affecting the service life of the catalyst. The activity, selectivity and service life of the catalyst constitute the overall performance of the catalyst. The methods listed above may have proposed better ways to improve the activity and selectivity of the catalyst, but they have not solved the problem of easy coking of the catalyst, or solved the problem of easy generation of green oil and coking of the catalyst, but did not solve the problem of selectivity. Although the carrier with a macroporous structure can improve the selectivity, the larger molecules generated by polymerization and chain growth reactions are also easily accumulated in the macropores of the carrier, causing the catalyst to coke and deactivate, affecting the service life of the catalyst.

[0008] In the selective hydrogenation reaction of carbon 2, when Pd is the main active component, in the traditional impregnation process of preparing the catalyst, Pd is 2+ or [PdCl4] 2- Pd is bound to the carrier in the form of ions. During the activation process, Pd aggregates to become active centers. Since the aggregation of Pd during the activation process is a random process governed by kinetics, the size of each active center is difficult to control in advance.

[0009] Previous studies have found that the selective hydrogenation process of acetylene is as follows: first, an acetylene molecule combines with a hydrogen atom to form a vinyl group, and then the vinyl group combines with a hydrogen atom to form ethylene, or two vinyl groups couple to form butadiene. Since butadiene can undergo a series of polymerization reactions to form green oil and then coke, inhibiting the formation of butadiene becomes the key to preventing coking of C2 selective hydrogenation catalysts.

[0010] Obviously, if two vinyl groups are formed simultaneously on one catalyst active center, the probability of butadiene formation will be greatly increased. Studies have also found that the larger the size of the active center, the higher the yield of butadiene. To prevent the active center from being large in size, there are generally two ways: one is to reduce the amount of active components, and the other is to expand the dispersion area of ​​the active components. However, reducing the loading amount of active components may result in insufficient number of active centers, resulting in insufficient hydrogenation activity, inability to completely remove acetylene, unqualified hydrogenation products, and huge economic losses.

[0011] The active component loading area is expanded, and some active centers are not located close to the catalyst surface, resulting in poor catalyst selectivity and large ethylene loss during the hydrogenation process.

[0012] In order to prepare catalysts with narrow particle size distribution, some researchers have synthesized a series of organic cages with three-dimensional structures in recent years. These organic cages have a fixed size and can be used to fix metals, thereby preparing catalysts with highly dispersed metal clusters. At present, these three-dimensional organic cages, after loading active components, are used in solution or evenly distributed on a carrier for full hydrogenation or homogeneous hydrogenation. For selective hydrogenation, not only the size of the active center affects the reaction, but also the distribution of the active components in the catalyst has a great influence on the reaction results. Catalysts with evenly distributed active components are not suitable for selective hydrogenation reactions.

[0013] At present, there are many studies on noble metal single-atom catalysts in hydrogenation reactions, but for the hydrogenation of alkynes, there is still a long way to go between this catalyst and practical application. The reason is that in the active center of the hydrogenation reaction, two processes need to be completed. One is the activation of the alkyne molecule, that is, the electron pair of the double bond of the alkyne molecule enters the empty orbit of the active center atom, and the active center atom feeds back the electron pair to the antibonding orbit of the alkyne molecule, causing the double bond energy to decrease, the double bond to be activated, and the breakage; at the same time, the hydrogen molecule also needs the same process to activate the hydrogen into hydrogen atoms. For the single-atom active center, due to the limited physical size of a single atom, it is difficult to complete the two processes at the same time, so its reaction process is slow and it is difficult to meet the requirements of practical application. Therefore, it is natural that the active neutral needs to have a certain physical size. In fact, for palladium catalysts, since a large amount of hydrogen can be absorbed inside its stacking structure, the activation of hydrogen and the transfer of hydrogen atoms are completed within the palladium stacking structure, so its activity is higher than that of active components that can only adsorb hydrogen on the surface. Summary of the invention

[0014] In order to solve the above technical problems, the purpose of the present invention is to provide an alkyne selective hydrogenation catalyst and a preparation method, wherein the catalyst is suitable for the acetylene selective hydrogenation process with the participation of CO.

[0015] To achieve the above object, the present invention provides a selective hydrogenation catalyst, wherein the active components of the catalyst contain Pd and Ag, and based on the mass of the carrier as 100%, the content of Pd is 0.045-0.075%, and the content of Ag is 0.06-0.12%;

[0016] The catalyst contains an organic cage, which is located on the outer surface of the catalyst and has a size of 2.7-3.6 nm. The Pd is loaded in the organic cage, and Ag is located in the middle or bottom of the Pd active center.

[0017] The catalyst of the present invention synthesizes an organic cage with a regular structure in situ on the outer surface of the carrier, the size of the cage is 2.7-3.6nm, and the active components are loaded in these organic cages. Limited by the size of the organic cage, the size of the active center is also uniform, which can meet the activity requirements and has no overly large active center. The probability of simultaneously adsorbing olefins and CO during acetylene hydrogenation is greatly reduced.

[0018] In the catalyst of the present invention, Ag can form an alloy with Pd to improve the selectivity of acetylene hydrogenation. Specifically, Ag has two functions: first, silver atoms separate palladium atoms, so that the spatial distance of adsorbed acetylene molecules is enlarged, and the corresponding reaction intermediates after acetylene hydrogenation are spaced relatively large, so that they do not form strongly adsorbed species of acetylene, and it is not easy for intermediate-vinyl coupling to occur, thereby reducing the formation of green oil, which is called geometric effect; second, the outer S electrons of silver enter the empty orbit of palladium, reducing the adsorption effect of palladium on ethylene, which is called electronic effect.

[0019] If the reaction material contains CO, since it is in a competitive adsorption relationship with acetylene, the probability of acetylene forming strong adsorption can be reduced, and the above-mentioned geometric effect can be played. Therefore, Ag may not be exposed on the outer surface of the catalyst. However, in order to improve the selectivity of the catalyst, the electronic effect of silver is still needed, so silver can exist inside or at the bottom of the active center of the catalyst.

[0020] According to a specific embodiment of the present invention, preferably, the specific surface area of ​​the catalyst is 15-30m 2 / g.

[0021] According to a specific embodiment of the present invention, preferably, the carrier of the catalyst is alumina or mainly alumina.

[0022] According to a specific embodiment of the present invention, preferably, the crystal form of the aluminum oxide in the carrier may be θ, α or a mixed crystal form thereof; and the aluminum oxide in the catalyst carrier is above 80%.

[0023] According to a specific embodiment of the present invention, preferably, the carrier further contains other metal oxides, such as magnesium oxide and / or titanium oxide.

[0024] The present invention also provides a method for preparing the above catalyst, which mainly comprises the following steps:

[0025] (1) forming a polar polymer within the carrier, which occupies 80-95% of the pore volume of the carrier;

[0026] (2) in situ synthesis of organic cages within the remaining outer pores of the support;

[0027] (3) loading the palladium active component in the organic cage, drying and then calcining to decompose the polar polymer formed in step (1);

[0028] (4) loading the active component silver;

[0029] (5) Loading palladium active components in the organic cage.

[0030] According to a specific embodiment of the present invention, preferably, the above preparation method comprises the following specific steps:

[0031] (1) mixing a hydrophilic polymerizable monomer with a calcined carrier and polymerizing the mixture at a certain temperature to obtain a first semi-finished catalyst, wherein the volume of the polymer synthesized from the hydrophilic monomer is 80-95% (preferably 85-95%) of the pore volume of the carrier;

[0032] (2) taking tri(4-formylphenyl)amine and halogenated acetic acid and mixing them, dissolving them in alkyl halide, and then mixing them with the first semi-finished catalyst, stirring and adding dropwise a mixed solution of an aromatic diamine compound and alkyl halide, allowing the mixture to stand, and after the reaction is complete, pouring out the residual liquid, washing with alcohol and deionized water respectively, and drying to obtain a second semi-finished catalyst;

[0033] The molar ratio of the aromatic diamine compound to tri(4-formylphenyl)amine is 1.2-2.5:1, and the mass ratio of tri(4-formylphenyl)amine to halogenated acetic acid is 2000-6000:1;

[0034] (3) dissolving an organic palladium salt in an organic solvent to obtain a first palladium precursor solution;

[0035] The second semi-finished product catalyst is immersed in an alcohol solution, the first solution of the palladium precursor is added dropwise to the mixture of the second semi-finished product catalyst and the alcohol, and stirred at the same time, and then a reducing agent is added dropwise, heated and stirred, and when the surface of the second semi-finished product catalyst no longer changes color, the solution is poured off, and the product is washed with deionized water, dried, and calcined at a temperature at which the polymer formed in step (1) can be decomposed to obtain a third semi-finished product catalyst;

[0036] (4) dissolving a soluble silver salt in deionized water or an organic solvent to obtain a silver-containing impregnation solution, immersing the third semi-finished catalyst in the silver-containing impregnation solution, allowing it to stand after it is completely absorbed, adding a reducing agent dropwise to reduce the silver, decanting the solution, washing with deionized water, and drying to obtain a fourth semi-finished catalyst;

[0037] (5) dissolving an organic palladium salt in an organic solvent to obtain a second palladium precursor solution, immersing the fourth semi-finished catalyst in an alcohol solution, and dropping the second palladium precursor solution into the mixture of the fourth semi-finished catalyst and the alcohol while stirring;

[0038] Add the reducing agent dropwise to the above solution, heat and stir, wait until the surface of the fourth semi-finished product catalyst no longer changes color, pour off the solution, wash and dry to obtain the catalyst, or, do not perform reduction, pour off the solution, wash with deionized water, dry, and calcine to obtain the catalyst.

[0039] According to a specific embodiment of the present invention, preferably, in the above preparation method, the mass ratio of the total mass of the organic palladium salt to tri(4-formylphenyl)amine in step (3) and step (5) is 2-14:1.

[0040] According to a specific embodiment of the present invention, preferably, in the above preparation method, step (4) is performed before step (3), and step (3) and step (5) are performed in combination.

[0041] According to a specific embodiment of the present invention, in order to obtain a catalyst with uniform active center size, the present invention first prepares an organic cage and then loads the active component palladium in the organic cage. The catalyst prepared in this way has an active center size within the range of 2.7-3.6 nm, which can avoid the formation of two vinyl groups on one active center or the simultaneous adsorption of CO and ethylene during the hydrogenation reaction.

[0042] If the synthesis process of the organic cage is carried out inside the carrier, the synthesized organic cage is evenly distributed on the carrier, and the active components of the catalyst after loading are also evenly distributed in all parts of the catalyst, it can only be used for full hydrogenation without considering selectivity, or homogeneous hydrogenation without diffusion limitation, and cannot be used for gas phase selective hydrogenation. In order to ensure that the organic cage is located on the outer surface of the carrier, the pores inside the carrier are occupied by other media in advance, so that the organic cage is synthesized in the pores close to the outer surface. In this way, in the obtained catalyst, the active component Pd is distributed in the organic cage, and the size of the active center is also within the appropriate range of 2.7-3.6nm, which can be suitable for gas phase selective hydrogenation reaction, especially the selective hydrogenation process of carbon distillation.

[0043] According to a specific embodiment of the present invention, the present invention does not limit the specific type of monomer used to synthesize the organic cage, as long as the size of the synthesized organic cage is between 2.7-3.6 nm. Preferably, in step (1), the hydrophilic polymerizable monomer is a monomer containing a carbonyl group and / or a carboxyl group and capable of polymerization or condensation reaction, more preferably comprising lactic acid, acrylic acid or formaldehyde.

[0044] According to a specific embodiment of the present invention, the certain temperature in step (1) refers to the temperature at which the monomer undergoes thermal condensation reaction or bulk polymerization, which varies with different monomers and is generally 80-200°C.

[0045] According to a specific embodiment of the present invention, the carrier in step (1) can be spherical, cylindrical, trifoliate, quadfoliate, etc.

[0046] According to a specific embodiment of the present invention, preferably, the decomposition temperature of the polymer formed by the hydrophilic polymerizable monomer is lower than 450°C, more preferably lower than 420°C.

[0047] According to a specific embodiment of the present invention, preferably, in step (2), the aromatic diamine is tetraphenyl diamine or a derivative thereof with a substituent on the benzene ring, preferably p-tetraphenyl diamine or a derivative thereof with a substituent on the benzene ring, and the substituent is preferably a halogen or an alkyl.

[0048] According to a specific embodiment of the present invention, preferably, the halogenated acetic acid is a catalyst for the reaction of tri(4-formylphenyl)amine with aromatic diamine compounds, and in step (2), the halogenated acetic acid is fluoroacetic acid or chloroacetic acid, preferably trifluoroacetic acid or dichloroacetic acid.

[0049] According to a specific embodiment of the present invention, preferably, the alkyl halide is the solvent required for the reaction. In step (2), the alkyl halide includes alkyl fluoride, alkyl chloride or alkyl bromide, more preferably methyl halide or ethyl halide, further preferably ethylene dichloride or chloroform.

[0050] According to a specific embodiment of the present invention, preferably, in step (3) and step (5), the organic palladium salt includes palladium acetate or palladium acetylacetonate;

[0051] When the organic palladium salt is palladium acetylacetonate, the organic solvent is chloroform; when the organic palladium salt is palladium acetate, the organic solvent is one or a combination of two or more of chloroform, dichloromethane and glacial acetic acid.

[0052] According to a specific embodiment of the present invention, preferably, in step (3) and step (5), the alcohol includes ethanol or methanol, more preferably ethanol.

[0053] According to a specific embodiment of the present invention, preferably, in step (3), step (4) and step (5), the reducing agent is a reducing compound, more preferably one or a combination of two or more of methanol, formaldehyde, formic acid, ethanol, acetaldehyde and hydrazine hydrate.

[0054] According to a specific embodiment of the present invention, preferably, in step (4), the soluble silver salt is a silver salt soluble in water or an organic solvent, more preferably silver nitrate soluble in water and / or silver acetylacetonate soluble in an organic solvent, etc. Ag is loaded by a solution method, such as a saturated impregnation method.

[0055] According to a specific embodiment of the present invention, after Ag is loaded in step (4), Pd is loaded in step (5), which can then be calcined to form an oxidized catalyst or directly reduced to form a reduced catalyst.

[0056] The present invention also provides a selective hydrogenation process for carbon distillation using crude hydrogen as a hydrogen source, which is carried out using the above catalyst.

[0057] The catalyst provided by the present invention has the following characteristics: since palladium is loaded in an organic cage, the maximum size of the active center composed of palladium is the size of the cage due to the limitation of the physical size of the cage, and the active center with a size greater than 3.0nm is reduced. This size meets the need for activity during acetylene selectivity, but the probability of forming two vinyl groups or CO and olefin adsorbing simultaneously in one active center is greatly reduced, the probability of hydroformylation reaction is reduced, the catalyst deactivation rate is delayed, the yield of butene can be reduced to less than 1 / 2 of that of traditional catalysts, and the generation of oxygen-containing compound aldehydes etc. is also greatly reduced. Moreover, the organic cage is located on the outer surface of the catalyst, avoiding the influence of internal diffusion restriction on the catalytic reaction, and the selectivity of the catalyst is very good. The catalyst of the present invention can reduce the generation of carbon four byproducts, and the carbonyl hydrogenation of oxygen-containing compounds reduces the generation of macromolecular oxygen-containing compounds.

[0058] Since by-products are greatly reduced, the catalyst prepared by this method may not even need to be regenerated. Even if it is regenerated, the catalyst can be regenerated at a temperature below 450°C, so as not to destroy the organic cage structure, ensure good performance of the hydrogenation process, and greatly extend the catalyst life. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 The pore size of the organic cage synthesized in Example 1 was measured using the BET method. DETAILED DESCRIPTION

[0060] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0061] The catalyst of the present invention is characterized by the following methods during preparation: BET measuring instrument, produced by Mack, USA, is used to measure the specific surface area and pore size distribution. The content of Pd and Ag in the catalyst is measured on A240FS atomic absorption spectrometer.

[0062] Agilent 7890A gas chromatograph was used to measure the hydrogen, acetylene and butene contents at the reactor outlet and inlet.

[0063] The catalyst weight was measured with a 0.1 mg electronic balance.

[0064] Raw materials: tri(4-formylphenyl)amine, dichloroacetic acid, dichloroethane, diphenylenediamine, hydrazine hydrate, ethanol, methanol, acetic acid, formic acid, formaldehyde, lactic acid, acrylic acid, palladium acetate, palladium acetylacetonate, silver nitrate, analytical grade, Shanghai Sinopharm Group Co., Ltd.; alumina, Shandong Aluminum Group Co., Ltd.

[0065] Example 1

[0066] This embodiment provides a catalyst, wherein:

[0067] Catalyst carrier: Commercially available spherical alumina carrier with a diameter of 4 mm was used. After calcination at 1080°C for 4 hours, the pore volume was 0.55 m 3 / g, specific surface area is 30m 2 Weigh 100 g of the carrier.

[0068] Catalyst preparation:

[0069] (1) Weighing 65.31 g of lactic acid and mixing it with 100 g of the calcined carrier, the mixture was kept at 160° C. for 10 hours to obtain a semi-finished catalyst A;

[0070] (2) 22.79 mg of tri(4-formylphenyl)amine and 0.00379 mg of dichloroacetic acid were mixed and dissolved in 60 ml of dichloroethane. The mixture was then mixed with the semi-finished catalyst A1, and a mixed solution of 27.54 mg of tetraphenyl diamine and 10 ml of dichloroethane was added dropwise while stirring. The mixture was allowed to stand at room temperature for 200 hours, the residue was decanted, and the mixture was washed with ethanol and deionized water, respectively, and dried to obtain a semi-finished catalyst B.

[0071] (3) 38 mg of palladium acetate was dissolved in 50 mL of glacial acetic acid. After the palladium acetate was completely dissolved, a palladium acetate solution was obtained. The semi-finished catalyst B was immersed in 50 mL of ethanol solution. The palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst B and ethanol while stirring. Then, 20 mL of a 40% formaldehyde solution was added dropwise to the mixture. The mixture was stirred at 70° C. for 1 hour. The solution was decanted, washed with deionized water, dried at 120° C., and calcined at 260° C. for 8 hours to obtain a semi-finished catalyst C.

[0072] (4) Weigh 0.11 g of silver nitrate and dissolve it in 52.3 g of deionized water. Immerse the semi-finished catalyst C in the prepared silver nitrate solution. After the solution is completely absorbed, let it stand for 4 hours. Then, add 5 ml of a 5% hydrazine hydrate solution dropwise to the solution. Stir at room temperature for 1 hour. Pour the solution out, wash with deionized water, and dry at 120° C. to obtain a semi-finished catalyst D.

[0073] (5) Dissolve 56.96 mg of palladium acetate in 50 mL of glacial acetic acid. After the palladium acetate is completely dissolved, a palladium acetate solution is obtained. The semi-finished catalyst D is immersed in 50 mL of ethanol solution. The palladium acetate solution is added dropwise to the mixture of the semi-finished catalyst D and ethanol while stirring. Then, 20 mL of a 40% formaldehyde solution is added dropwise to the mixture. The mixture is stirred at 70° C. for 1 hour. The solution is decanted, the mixture is washed with deionized water, and dried at 120° C. to obtain the desired catalyst.

[0074] The pore size of the organic cage synthesized in Example 1 measured by the BET method is as follows: Figure 1 As shown. Figure 1 It can be seen that the maximum pore size is 3.53 nm and the minimum pore size is 2.91 nm.

[0075] The Pd content of the catalyst prepared in Example 1 was determined by atomic absorption spectrometry to be 0.045%, and the Ag content was 0.07%.

[0076] Comparative Example 1

[0077] This comparative example provides a catalyst, wherein:

[0078] Catalyst carrier: The carrier used in Example 1 was adopted.

[0079] Catalyst preparation: The preparation process conditions are the same as those in Example 1, except that no silver is loaded;

[0080] (1) Weighing 65.30 g of lactic acid and mixing it with 100 g of the calcined carrier, the mixture was kept at 160° C. for 10 hours to obtain a semi-finished catalyst A1;

[0081] (2) 22.79 mg of tri(4-formylphenyl)amine and 0.00379 mg of dichloroacetic acid were mixed and dissolved in 60 ml of dichloroethane. The mixture was then mixed with the semi-finished catalyst A1, and a mixed solution of 27.54 mg of tetraphenyl diamine and 10 ml of dichloroethane was added dropwise while stirring. The mixture was allowed to stand at room temperature for 200 hours, the residual liquid was decanted, and the mixture was washed with ethanol and deionized water, respectively, and dried to obtain the semi-finished catalyst B1;

[0082] (3) 38 mg of palladium acetate was dissolved in 50 mL of glacial acetic acid. After the palladium acetate was completely dissolved, a palladium acetate solution was obtained. The semi-finished catalyst B1 was immersed in 50 mL of ethanol solution. The palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst B1 and ethanol while stirring. Then, 20 mL of a 40% formaldehyde solution was added dropwise to the mixture. The mixture was stirred at 70° C. for 1 hour. The solution was decanted, washed with deionized water, dried at 120° C., and calcined at 260° C. for 8 hours to obtain a semi-finished catalyst C1.

[0083] (4) 56.96 mg of palladium acetate was dissolved in 50 mL of glacial acetic acid. After the palladium acetate was completely dissolved, a palladium acetate solution was obtained. The semi-finished catalyst C1 was immersed in 50 mL of ethanol solution. The palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst C1 and ethanol while stirring. Then, 20 mL of a 40% formaldehyde solution was added dropwise to the mixture. The mixture was stirred at 70° C. for 1 hour. The solution was decanted, the mixture was washed with deionized water, and dried at 120° C. to obtain the desired catalyst.

[0084] The Pd content in the catalyst prepared in Comparative Example 1 was determined by atomic absorption spectroscopy to be 0.045%.

[0085] Example 2

[0086] This embodiment provides a catalyst, wherein:

[0087] Carrier: Commercially available spherical alumina carrier with a diameter of 3 mm was used. After calcination at 1150°C for 4 hours, the water absorption rate and pore volume were 0.65 m 3 / g, specific surface area is 15.07m 2 Weigh 100 g of the carrier.

[0088] Catalyst preparation:

[0089] (1) Weigh 73.7 g of lactic acid and mix with 100 g of the calcined carrier, and keep the mixture at 200° C. for 10 hours to obtain a semi-finished catalyst E;

[0090] (2) 3.57 mg of tri(4-formylphenyl)amine and 0.0017 mg of dichloroacetic acid were mixed and dissolved in 60 ml of dichloroethane. The mixture was then mixed with the semi-finished catalyst E. The mixture was stirred and a mixed solution of 8.89 mg of tetraphenyl diamine and 10 ml of trichloroethane was added dropwise. The mixture was allowed to stand at room temperature for 200 hours. The residue was decanted and washed with ethanol and deionized water, respectively, and dried to obtain a semi-finished catalyst F.

[0091] (3) 28.6 mg of palladium acetylacetonate was dissolved in 50 mL of chloroform. After the palladium acetylacetonate was completely dissolved, a palladium acetylacetonate solution was obtained. The semi-finished catalyst F was immersed in 50 mL of ethanol solution. The palladium acetylacetonate solution was added dropwise to the mixture of the semi-finished catalyst F and ethanol while stirring. Then, 20 mL of a 40% formaldehyde solution was added dropwise to the mixture. The mixture was stirred at 70° C. for 1 hour. The solution was decanted, washed with deionized water, dried at 120° C., and calcined at 300° C. for 8 hours to obtain a semi-finished catalyst G.

[0092] (4) Weigh 0.094 g of silver nitrate and dissolve it in 65 g of deionized water. Immerse the semi-finished catalyst G in the prepared silver nitrate solution. After the solution is completely absorbed, let it stand for 4 hours. Then, add 5 ml of 5% hydrazine hydrate solution dropwise to the above solution. Stir at room temperature for 1 hour, pour off the solution, wash with deionized water, and dry at 120° C. to obtain the desired catalyst. The semi-finished catalyst H is obtained.

[0093] (5) 114.58 mg of palladium acetylacetonate was dissolved in 50 mL of chloroform. After the palladium acetylacetonate was completely dissolved, the semi-finished catalyst H was immersed in 50 mL of ethanol solution. The palladium acetylacetonate solution was added dropwise to the mixture of the semi-finished catalyst H and ethanol while stirring. Then, 20 mL of a 40% formaldehyde solution was added dropwise to the mixture. The mixture was stirred at 70° C. for 1 hour. The solution was decanted, the mixture was washed with deionized water, and dried at 120° C. to obtain the desired catalyst.

[0094] The Pd content of the catalyst prepared in Example 2 was determined by atomic absorption spectrometry to be 0.05% and the Ag content to be 0.06%.

[0095] Comparative Example 2

[0096] This comparative example provides a catalyst, wherein:

[0097] Carrier: The same carrier as in Example 2 was used.

[0098] Catalyst preparation: The preparation conditions are the same as those in Example 2, except that all the palladium is loaded in step (3);

[0099] (1) Weigh 73.7 g of lactic acid and mix with 100 g of the calcined carrier, and keep the mixture at 200° C. for 10 hours to obtain a semi-finished catalyst E1;

[0100] (2) 3.57 mg of tri(4-formylphenyl)amine and 0.0017 mg of dichloroacetic acid were mixed and dissolved in 60 ml of dichloroethane. The mixture was then mixed with the semi-finished catalyst E, and a mixed solution of 8.89 mg of tetraphenyl diamine and 10 ml of trichloroethane was added dropwise while stirring. The mixture was allowed to stand at room temperature for 200 hours, the residue was decanted, and the mixture was washed with ethanol and deionized water, respectively, and dried to obtain the semi-finished catalyst F1.

[0101] (3) 143.18 mg of palladium acetylacetonate was dissolved in 50 mL of chloroform. After the palladium acetylacetonate was completely dissolved, a palladium acetylacetonate solution was obtained. The semi-finished catalyst F1 was immersed in 50 mL of the ethanol solution. The palladium acetylacetonate solution was added dropwise to the mixture of the semi-finished catalyst F1 and ethanol while stirring. Then, 20 mL of a 40% formaldehyde solution was added dropwise to the mixture. The mixture was stirred at 70° C. for 1 hour. The solution was decanted, the mixture was washed with deionized water, dried at 120° C., and calcined at 300° C. for 8 hours to obtain a semi-finished catalyst G1.

[0102] (4) Weigh 0.094 g of silver nitrate and dissolve it in 65 g of deionized water. Immerse the semi-finished catalyst G1 in the prepared silver nitrate solution. After the solution is completely absorbed, let it stand for 4 hours. Then, add 5 ml of 5% hydrazine hydrate solution dropwise to the above solution. Stir at room temperature for 1 hour, pour off the solution, wash with deionized water, and dry at 120° C. to obtain the desired catalyst.

[0103] The Pd content of the catalyst prepared in Comparative Example 2 was determined by atomic absorption spectroscopy to be 0.05% and the Ag content to be 0.06%.

[0104] Example 3

[0105] This embodiment provides a catalyst, wherein:

[0106] Support: A commercially available spherical alumina-titania support was used, with a titanium oxide content of 20% and a diameter of 4 mm. After calcination at 1105°C for 4 hours, the pore volume was 0.50 m 3 / g, specific surface area is 25.14m 2 Weigh 100 g of the carrier.

[0107] Catalyst preparation:

[0108] (1) 18.9 g of acrylic acid, 26 g of water, 0.01 g of potassium hypophosphite monohydrate, 0.023 g of copper acetate monohydrate, and 0.16 ml of 35% hydrogen peroxide as an initiator were weighed and mixed evenly, and 100 g of the calcined carrier was added. After the solution was completely absorbed, the mixture was transferred to a reflux bottle and heated to 80° C. under stirring for 1 hour to obtain a semi-finished catalyst I;

[0109] (2) 16.25 mg of tri(4-formylphenyl)amine and 0.00325 mg of trichloroacetic acid were mixed and dissolved in 50 ml of dichloroethane, and then mixed with the semi-finished catalyst I. After stirring, a mixed solution of 33.15 mg of tetraphenyl diamine and 10 ml of trichloroethane was added dropwise. The mixture was allowed to stand at room temperature for 150 hours, the residue was decanted, and the mixture was washed with ethanol and deionized water, respectively, and dried to obtain a semi-finished catalyst J.

[0110] (3) 29.13 mg of palladium acetylacetonate was dissolved in 50 ml of chloroform. After the palladium acetylacetonate was completely dissolved, a palladium acetylacetonate solution was obtained. The semi-finished catalyst J was immersed in 50 ml of ethanol solution. The palladium acetylacetonate solution was added dropwise to the mixture of the semi-finished catalyst J and ethanol while stirring. Then, 10 ml of a 50% formic acid solution was added dropwise to the mixture. The mixture was heated and stirred at 70° C. for 2 hours. The solution was decanted, washed with deionized water, dried at 120° C., and calcined at 400° C. for 2 hours to obtain a semi-finished catalyst K.

[0111] (4) Dissolve 0.16 g of silver nitrate in 45 g of deionized water, immerse the semi-finished catalyst K in the prepared silver nitrate solution, let stand for 4 hours after the solution is completely absorbed, add 5 ml of 10% hydrazine hydrate solution dropwise to the above solution, stir at room temperature for 1 hour, pour off the solution, wash with deionized water, and dry at 120° C. to obtain the semi-finished catalyst M.

[0112] (5) Dissolve 156.84 mg of palladium acetylacetonate in 50 ml of chloroform. After the palladium acetylacetonate is completely dissolved, immerse the semi-finished catalyst M in 50 ml of ethanol solution. Add the prepared palladium acetylacetonate solution dropwise to the mixture of the semi-finished catalyst M and ethanol while stirring. Then, add 10 ml of a 50% formic acid solution dropwise to the mixture. Heat and stir at 70° C. for 2 hours. Pour off the solution, wash with deionized water, dry at 120° C., and calcine at 400° C. for 2 hours to obtain the desired catalyst.

[0113] The Pd content of the catalyst prepared in Example 3 was determined by atomic absorption spectroscopy to be 0.065%, and the Ag content was 0.1%.

[0114] Comparative Example 3

[0115] This comparative example provides a catalyst, wherein:

[0116] Carrier: The same carrier as in Example 3 was used.

[0117] Catalyst preparation: The catalyst preparation conditions are the same as those in Example 3, except that the amount of tri(4-formylphenyl)amine in Comparative Example 3 is 4 times higher than that in Example 3;

[0118] (1) 18.9 g of acrylic acid, 26 g of water, 0.01 g of potassium hypophosphite monohydrate, 0.023 g of copper acetate monohydrate, and 0.16 ml of 35% hydrogen peroxide were weighed as an initiator, mixed evenly, and 100 g of the calcined carrier was added. After the solution was completely absorbed, the mixture was transferred to a reflux bottle and heated to 80° C. under stirring for 1 hour to obtain a semi-finished catalyst I1;

[0119] (2) 65 mg of tri(4-formylphenyl)amine and 0.00325 mg of trichloroacetic acid were mixed and dissolved in 50 ml of dichloroethane, and then mixed with the semi-finished catalyst I1. After stirring, a mixed solution of 33.15 mg of tetraphenyl diamine and 10 ml of trichloroethane was added dropwise. The mixture was allowed to stand at room temperature for 150 hours, the residue was poured out, and the mixture was washed with ethanol and deionized water, respectively, and dried to obtain the semi-finished catalyst J1.

[0120] (3) 29.13 mg of palladium acetylacetonate was dissolved in 50 ml of chloroform. After the palladium acetylacetonate was completely dissolved, a palladium acetylacetonate solution was obtained. The semi-finished catalyst J1 was immersed in 50 ml of ethanol solution. The palladium acetylacetonate solution was added dropwise to the mixture of the semi-finished catalyst J1 and ethanol while stirring. Then, 10 ml of a 50% formic acid solution was added dropwise to the mixture. The mixture was heated and stirred at 70° C. for 2 hours. The solution was decanted, washed with deionized water, dried at 120° C., and calcined at 400° C. for 2 hours to obtain a semi-finished catalyst K1.

[0121] (4) 0.16 g of silver nitrate was dissolved in 45 g of deionized water, and the semi-finished catalyst K1 was immersed in the prepared silver nitrate solution. After the solution was completely absorbed, it was allowed to stand for 4 hours. 5 ml of 10% hydrazine hydrate solution was added dropwise to the above solution, and stirred at room temperature for 1 hour. The solution was decanted, washed with deionized water, and dried at 120° C. to obtain the semi-finished catalyst M1.

[0122] (5) Dissolve 156.84 mg of palladium acetylacetonate in 50 ml of chloroform. After the palladium acetylacetonate is completely dissolved, immerse the semi-finished catalyst M1 in 50 ml of ethanol solution. Add the prepared palladium acetylacetonate solution dropwise to the mixture of the semi-finished catalyst M1 and ethanol while stirring. Then, add 10 ml of a 50% formic acid solution dropwise to the mixture. Heat and stir at 70°C for 2 hours. Pour off the solution, wash with deionized water, dry at 120°C, and calcine at 400°C for 2 hours to obtain the desired catalyst.

[0123] The Pd content of the catalyst prepared in Comparative Example 3 was 0.065% and the Ag content was 0.1% as determined by atomic absorption spectroscopy.

[0124] Example 4

[0125] This embodiment provides a catalyst, wherein:

[0126] Support: A commercially available toothed ball-shaped alumina-magnesia support was used, with a magnesium oxide content of 5% and a diameter of 3 mm. After calcination at 1135°C for 4 hours, the pore volume was 0.55 m 3 / g, specific surface area is 22.39m 2 Weigh 100 g of the carrier.

[0127] Catalyst preparation:

[0128] (1) Weigh 58.43 g of lactic acid and mix it with 100 g of the calcined carrier, and keep it at 190° C. for 2 hours to obtain a semi-finished catalyst N;

[0129] (2) 10.7 mg of tri(4-formylphenyl)amine and 0.0018 mg of trifluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane, then mixed with semi-finished catalyst N, stirred and a mixed solution of 14.9 mg of tetraphenyl diamine and 10 ml of dichloroethane was added dropwise, the mixture was allowed to stand at room temperature for 180 hours, the residue was poured out, and the mixture was washed with ethanol and deionized water respectively, and dried to obtain semi-finished catalyst O;

[0130] (3) 94.95 mg of palladium acetate was dissolved in 50 ml of chloroform, and the palladium acetate was completely dissolved and set aside. The semi-finished catalyst O was immersed in 50 ml of ethanol solution, and the prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst O and ethanol while stirring, and then 20 ml of 80% or more methanol solution was added dropwise to the above mixture, and stirred at 80°C for 1 hour, the solution was decanted, and the mixture was washed with deionized water, dried at 120°C, and calcined at 420°C for 1 hour to obtain the semi-finished catalyst P.

[0131] (4) 0.189 g of silver nitrate was dissolved in 53 g of deionized water, and the semi-finished catalyst P was immersed in the prepared silver nitrate solution. After the solution was completely absorbed, it was allowed to stand for 4 hours. Then 5 ml of a 5% hydrazine hydrate solution was added dropwise to the above solution. The solution was stirred at room temperature for 1 hour, the solution was decanted, the catalyst was washed with deionized water, and dried at 120° C. to obtain a semi-finished catalyst Q.

[0132] (5) Dissolve 63.31 mg of palladium acetate in 50 ml of chloroform, and wait until the palladium acetate is completely dissolved and set aside. Immerse the semi-finished catalyst Q in 50 ml of ethanol solution, drop the prepared palladium acetate solution into the mixture of the semi-finished catalyst Q and ethanol, and stir at the same time, then drop 20 ml of 80% or more methanol solution into the above mixture, stir at 80°C for 1 hour, pour off the solution, wash with deionized water, dry at 120°C, and calcine at 400°C for 1 hour to obtain the desired catalyst.

[0133] The Pd content of the catalyst prepared in Example 4 was determined by atomic absorption spectroscopy to be 0.075% and the Ag content to be 0.12%.

[0134] Comparative Example 4

[0135] This comparative example provides a catalyst, wherein:

[0136] Support: The catalyst support is the same as in Example 4.

[0137] Catalyst preparation: This comparative example differs from Example 4 in that step (1) is omitted.

[0138] (1) 10.7 mg of tri(4-formylphenyl)amine and 0.0018 mg of trifluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane, then mixed with the carrier, stirred and a mixed solution of 14.9 mg of tetraphenyl diamine and 10 ml of dichloroethane was added dropwise, the mixture was allowed to stand at room temperature for 180 hours, the residual liquid was poured out, and the mixture was washed with ethanol and deionized water respectively, and dried to obtain a semi-finished catalyst O1;

[0139] (2) 94.95 mg of palladium acetate was dissolved in 50 ml of chloroform, and the palladium acetate was completely dissolved and set aside. The semi-finished catalyst O1 was immersed in 50 ml of ethanol solution, and the prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst O1 and ethanol while stirring, and then 20 ml of 80% or more methanol solution was added dropwise to the above mixture, and stirred at 80°C for 1 hour, the solution was decanted, and the mixture was washed with deionized water, dried at 120°C, and calcined at 420°C for 1 hour to obtain the semi-finished catalyst P1.

[0140] (3) 0.189 g of silver nitrate was dissolved in 53 g of deionized water, and the semi-finished catalyst P1 was immersed in the prepared silver nitrate solution. After the solution was completely absorbed, it was allowed to stand for 4 hours. Then 5 ml of a 5% hydrazine hydrate solution was added dropwise to the above solution. The mixture was stirred at room temperature for 1 hour, the solution was decanted, the mixture was washed with deionized water, and dried at 120° C. to obtain the semi-finished catalyst Q1.

[0141] (4) Dissolve 63.31 mg of palladium acetate in 50 ml of chloroform, and wait until the palladium acetate is completely dissolved and set aside. Immerse the semi-finished catalyst Q1 in 50 ml of ethanol solution, drop the prepared palladium acetate solution into the mixture of the semi-finished catalyst Q1 and ethanol, and stir at the same time, then drop 20 ml of 80% or more methanol solution into the above mixture, stir at 80°C for 1 hour, pour off the solution, wash with deionized water, dry at 120°C, and calcine at 400°C for 1 hour to obtain the desired catalyst.

[0142] The Pd content of the catalyst prepared in Comparative Example 4 was determined by atomic absorption spectroscopy to be 0.075% and the Ag content to be 0.12%.

[0143] Example 5

[0144] This embodiment provides a catalyst, wherein:

[0145] Support: Spherical alumina-magnesia support with a magnesium oxide content of 10% and a diameter of 3 mm. After calcination at 1100°C for 4 hours, the pore volume is 0.53 m 3 / g, specific surface area 28.68m 2 Weigh 100 g of the carrier.

[0146] Catalyst preparation:

[0147] (1) Weigh 63.90 g of lactic acid and mix it with 100 g of the calcined carrier, and keep it at 180° C. for 2 hours to obtain a semi-finished catalyst R;

[0148] (2) 11.67 mg of tri(4-formylphenyl)amine and 0.0047 mg of dichloroacetic acid were mixed and dissolved in 50 ml of dichloroethane, then mixed with the semi-finished catalyst R, stirred and a mixed solution of 26.19 mg of tetraphenyl diamine and 10 ml of dichloroethane was added dropwise, the mixture was allowed to stand at room temperature for 190 hours, the residue was poured out, and the semi-finished catalyst S was obtained by washing with ethanol and deionized water respectively;

[0149] (3) Dissolve 100 mg of palladium acetylacetonate in 50 ml of benzene, and wait until the palladium acetylacetonate is completely dissolved and set aside. Immerse the semi-finished catalyst S in 50 ml of 80% or more methanol solution, drop the prepared palladium acetylacetonate solution into the mixture of the semi-finished catalyst S and methanol, and stir at the same time, then drop 10 ml of about 40% formaldehyde solution into the above mixture, stir at 50°C for 1 hour, pour off the solution, wash with deionized water, dry at 120°C, and calcine at 380°C for 1 hour to obtain the semi-finished catalyst T.

[0150] (4) 0.141 g of silver nitrate was dissolved in 53 g of deionized water, and the semi-finished catalyst T was immersed in the prepared silver nitrate solution. After the solution was completely absorbed, it was allowed to stand for 4 hours. Then 20 ml of a 50% formic acid solution was added dropwise to the above solution, and the mixture was stirred at 50° C. for 1 hour. The solution was decanted, the mixture was washed with deionized water, and dried at 120° C. to obtain a semi-finished catalyst U.

[0151] (5) Dissolve 100 mg of palladium acetylacetonate in 50 ml of benzene, wait until the palladium acetylacetonate is completely dissolved, and set aside. Immerse the semi-finished catalyst U in 50 ml of methanol solution, drop the prepared palladium acetylacetonate solution into the mixture of the semi-finished catalyst U and methanol, and stir at the same time, then drop 10 ml of a 40% formaldehyde solution into the above mixture, stir at 50°C for 1 hour, pour off the solution, wash with deionized water, dry at 120°C, and calcine at 380°C for 1 hour to obtain the desired catalyst.

[0152] The Pd content of the catalyst prepared in Example 5 was determined by atomic absorption spectrometry to be 0.07% and the Ag content to be 0.09%.

[0153] Comparative Example 5

[0154] This comparative example provides a catalyst, wherein the catalyst carrier is the same as that in Example 5, except that the catalyst is prepared by a traditional method.

[0155] (1) Weigh 116.67 mg of palladium chloride and dissolve it in 80 ml of deionized water. Adjust the pH to 2.5. Immerse 100 g of the calcined support in the solution. After 30 min, dry at 120° C. and calcine at 500° C. to obtain a semi-finished catalyst T1.

[0156] (2) Weigh 142.16 mg of silver nitrate and dissolve it in 52.25 g of deionized water to obtain a silver nitrate solution. Immerse the semi-finished catalyst T1 in the prepared silver nitrate solution. After the solution is completely absorbed, dry it at 100° C. and calcine it at 550° C. to obtain the desired catalyst.

[0157] The Pd content of the catalyst prepared in Comparative Example 5 was determined by atomic absorption spectroscopy to be 0.07% and the Ag content to be 0.09%.

[0158] Example 6

[0159] This embodiment provides a catalyst, wherein:

[0160] Support: A commercially available spherical support is used, with 95% alumina and 5% titanium oxide, and a diameter of 3 mm. After calcination at 1090°C for 4 hours, the pore volume is 0.48 m 3 / g, specific surface area is 30.13m 2 Weigh 100 g of the carrier.

[0161] Catalyst preparation:

[0162] (1) Weighing 57.14 g of lactic acid and mixing it with 100 g of the calcined carrier, the mixture was kept at 190° C. for 1 hour to obtain a semi-finished catalyst V;

[0163] (2) 8.13 mg of tri(4-formylphenyl)amine and 0.0023 mg of trifluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane, and then mixed with the semi-finished catalyst V. A mixed solution of 15.46 mg of 3-methylquaterphenylenediamine and 10 ml of dichloroethane was added dropwise while stirring. The mixture was allowed to stand at room temperature for 100 hours, the residue was decanted, and the mixture was washed with ethanol and deionized water, respectively, and dried to obtain the semi-finished catalyst W;

[0164] (3) Weigh 173.23 mg of silver nitrate and dissolve it in 48 g of deionized water. Immerse the semi-finished catalyst W in the prepared solution. After the solution is completely absorbed, let it stand for 4 hours. Then, add 50 ml of 50% or more acetaldehyde solution dropwise to the above solution. Stir at 60° C. for 1 hour. Pour off the solution, wash with deionized water, and dry at 120° C. to obtain the semi-finished catalyst Y.

[0165] (4) 137.16 mg of palladium acetate was dissolved in 50 ml of dichloroethane. The solution was prepared and used for later use. The semi-finished catalyst Y was immersed in 50 ml of ethanol solution. The prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst Y and ethanol while stirring. Then 30 ml of 50% or more acetaldehyde solution was added dropwise to the mixture. The mixture was stirred at 60° C. for 1 hour. The solution was decanted, washed with deionized water, and dried at 120° C. to obtain the desired catalyst.

[0166] The Pd content of the catalyst prepared in Example 6 was determined by atomic absorption spectroscopy to be 0.065%, and the Ag content was 0.11%.

[0167] Comparative Example 6

[0168] This comparative example provides a catalyst, wherein:

[0169] Carrier: The same carrier as in Example 6 was used. The difference from Example 6 was that phenylenediamine with the same molar number as 3-methyltetraphenylenediamine was used to prepare the organic cage with tri(4-formylphenyl)amine.

[0170] Catalyst preparation:

[0171] (1) Weigh 57.14 g of lactic acid and mix with 100 g of the calcined carrier, and keep the mixture at 190° C. for 1 hour to obtain a semi-finished catalyst V1;

[0172] (2) 8.13 mg of tri(4-formylphenyl)amine and 0.0023 mg of trifluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane. The mixture was then mixed with the semi-finished catalyst V1. A mixed solution of 4.80 mg of phenylenediamine and 10 ml of dichloroethane was added dropwise while stirring. The mixture was allowed to stand at room temperature for 100 hours. The residue was decanted and washed with ethanol and deionized water, respectively, and dried to obtain the semi-finished catalyst W1.

[0173] (3) Weigh 173.23 mg of silver nitrate and dissolve it in 48 g of deionized water. Immerse the semi-finished catalyst W1 in the prepared solution. After the solution is completely absorbed, let it stand for 4 hours. Then, add 50 ml of 50% or more acetaldehyde solution dropwise to the above solution. Stir at 60° C. for 1 hour. Pour off the solution, wash with deionized water, and dry at 120° C. to obtain the semi-finished catalyst Y1.

[0174] (4) 137.16 mg of palladium acetate was dissolved in 50 ml of dichloroethane. The solution was set aside after the palladium acetate was completely dissolved. The semi-finished catalyst Y1 was immersed in 50 ml of ethanol solution. The prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst Y1 and ethanol while stirring. Then 30 ml of 50% or more acetaldehyde solution was added dropwise to the mixture. The mixture was stirred at 60° C. for 1 hour. The solution was decanted, washed with deionized water, and dried at 120° C. to obtain the desired catalyst.

[0175] The Pd content of the catalyst prepared in Comparative Example 6 was determined by atomic absorption spectroscopy to be 0.065%, and the Ag content to be 0.11%.

[0176] Example 7

[0177] This embodiment provides a catalyst, wherein:

[0178] Carrier: Commercially available spherical alumina carrier with a diameter of 4 mm was used. After calcination at 1135°C for 4 hours, the water absorption rate and pore volume were 0.60 m 3 / g, specific surface area is 21.75m 2 Weigh 100 g of the carrier.

[0179] Catalyst preparation:

[0180] (1) Weigh 67.5 g of lactic acid and mix it with 100 g of the calcined carrier, and keep it at 210° C. for 2 hours to obtain a semi-finished catalyst AA;

[0181] (2) 17.14 mg of tri(4-formylphenyl)amine and 0.0057 mg of difluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane, then mixed with semi-finished catalyst AA, stirred and dripped with a mixed solution of 42.40 mg of 2-chloroquaterphenylenediamine and 10 ml of dichloroethane, and the mixture was allowed to stand at room temperature for 120 hours, the residual liquid was poured out, and the semi-finished catalyst BB was obtained by washing with ethanol and deionized water respectively;

[0182] (3) Weigh 51.53 mg of palladium acetate and dissolve it in 50 ml of dichloroethane. Wait until the palladium acetate is completely dissolved to obtain a palladium acetate solution.

[0183] The semi-finished catalyst BB was immersed in 50 ml of ethanol solution, and the prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst BB and methanol while stirring. Then, 3 ml of 5% hydrazine hydrate solution was added dropwise to the above mixture, and stirred at room temperature for 1 hour. The solution was poured off, washed with deionized water, dried at 120°C, and calcined at 300°C for 2 hours to obtain the semi-finished catalyst CC.

[0184] (4) Weigh 0.23 g of silver acetylacetonate and dissolve it in 60 ml of toluene. Immerse the semi-finished catalyst CC in the prepared silver acetylacetonate solution. After the solution is completely absorbed, let it stand for 4 hours. Then, add 3 ml of a 5% hydrazine hydrate solution dropwise to the solution. Stir at room temperature for 1 hour. Pour the solution out, wash with deionized water, and dry at 120° C. to obtain a semi-finished catalyst DD.

[0185] (5) Weigh 73.47 mg of palladium acetate and dissolve it in 50 ml of dichloroethane. Wait until the palladium acetate is completely dissolved to obtain a palladium acetate solution.

[0186] Immerse the semi-finished catalyst DD in 50 ml of ethanol solution, add the prepared palladium acetate solution dropwise to the mixture of the semi-finished catalyst DD and methanol while stirring, then add 3 ml of 5% hydrazine hydrate solution dropwise to the above mixture, stir at room temperature for 1 hour, pour off the solution, wash with deionized water, dry at 120°C, and calcine at 300°C for 2 hours to obtain the desired catalyst.

[0187] The Pd content of the catalyst prepared in Example 7 was determined by atomic absorption spectroscopy to be 0.06%, and the Ag content to be 0.12%.

[0188] Comparative Example 7

[0189] This comparative example provides a catalyst, wherein:

[0190] Carrier: The same carrier as in Example 7 was used.

[0191] Catalyst preparation: The preparation conditions are the same as those in Example 7, except that the calcination temperature in step (3) is 600°C.

[0192] (1) Weigh 67.5 g of lactic acid and mix it with 100 g of the calcined carrier, and keep it at 210° C. for 2 hours to obtain a semi-finished catalyst AA1;

[0193] (2) 17.14 mg of tri(4-formylphenyl)amine and 0.0057 mg of difluoroacetic acid were mixed and dissolved in 50 ml of dichloroethane, and then mixed with the semi-finished catalyst AA1. The mixture was stirred and a mixed solution of 42.40 mg of 2-chloroquaterphenylenediamine and 10 ml of dichloroethane was added dropwise. The mixture was allowed to stand at room temperature for 120 hours, the residual liquid was poured out, and the mixture was washed with ethanol and deionized water, respectively, and dried to obtain the semi-finished catalyst BB1.

[0194] (3) Weigh 51.53 mg of palladium acetate and dissolve it in 50 ml of dichloroethane. Wait until the palladium acetate is completely dissolved to obtain a palladium acetate solution.

[0195] The semi-finished catalyst BB1 was immersed in 50 ml of ethanol solution, and the prepared palladium acetate solution was added dropwise to the mixture of the semi-finished catalyst BB1 and methanol while stirring. Then 3 ml of 5% hydrazine hydrate solution was added dropwise to the above mixture, and stirred at room temperature for 1 hour. The solution was poured off, washed with deionized water, dried at 120°C, and calcined at 600°C for 2 hours to obtain the semi-finished catalyst CC1.

[0196] (4) Weigh 0.23 g of silver acetylacetonate and dissolve it in 60 ml of toluene. Immerse the semi-finished catalyst CC1 in the prepared silver acetylacetonate solution. After the solution is completely absorbed, let it stand for 4 hours. Then, add 3 ml of a 5% hydrazine hydrate solution dropwise to the solution. Stir at room temperature for 1 hour, pour off the solution, wash with deionized water, and dry at 120° C. to obtain the semi-finished catalyst DD1.

[0197] (5) Weigh 73.47 mg of palladium acetate and dissolve it in 50 ml of dichloroethane. Wait until the palladium acetate is completely dissolved to obtain a palladium acetate solution.

[0198] Immerse the semi-finished catalyst DD1 in 50 ml of ethanol solution, add the prepared palladium acetate solution dropwise to the mixture of the semi-finished catalyst DD1 and methanol while stirring, then add 3 ml of 5% hydrazine hydrate solution dropwise to the above mixture, stir at room temperature for 1 hour, pour off the solution, wash with deionized water, dry at 120°C, and calcine at 300°C for 2 hours to obtain the desired catalyst.

[0199] The Pd content of the catalyst prepared in Comparative Example 7 was determined by atomic absorption spectroscopy to be 0.06% and the Ag content to be 0.12%.

[0200] Performance of catalysts for C2 post-hydrogenation

[0201] Evaluation method:

[0202] The catalyst loading amount in the fixed bed single-stage reactor is 100 mL (recorded weight), the filler is 50 mL, the reaction material space velocity is 4000 / h, the operating pressure is 2.5 MPa, the hydrogen-acetylene ratio is 1.5, and the reactor inlet temperature is 75°C.

[0203] Catalyst reduction: hydrogen flow rate 10 L / h, constant temperature 130°C for 4 hours.

[0204] The calculation method of the evaluation results is shown in Table 1.

[0205] Table 1 Calculation method of evaluation results

[0206]

[0207] The initial selectivity is the selectivity measured 24 hours after the reactor is charged.

[0208] The initial activity is the activity (acetylene conversion rate) measured 24 hours after the reactor is charged.

[0209] The reaction material composition is as follows:

[0210] Acetylene 0.9% (mol / mol), ethylene 82% (mol / mol), ethane 17% (mol / mol), CO 200ppm, C3 content 0.5% (mol / mol).

[0211] The catalyst evaluation results are shown in Table 2.

[0212] Table 2 Catalyst evaluation results

[0213]

[0214]

[0215] From the comparison of the catalyst evaluation results in Table 2, it can be seen that:

[0216] Compared with Example 1, the selectivity of Comparative Example 1 is at least 5 percentage points lower due to the lack of silver loading.

[0217] In Comparative Example 2, since all the palladium was loaded first and the silver was loaded later, part of the active sites on the surface of the active center were occupied by silver, and the ability to adsorb alkynes decreased. Compared with Example 2, the catalytic activity was greatly reduced.

[0218] In Comparative Example 3, the amount of tri(4-formylphenyl)amine was greatly increased, the number of organic cages formed in the early stage of synthesis increased, the number of corresponding active centers was too large, and the size of the palladium active center loaded by a single organic cage became smaller, resulting in insufficient catalyst activity.

[0219] In Comparative Example 4, polar polymers were not synthesized in the carrier in advance, and the synthesis reaction of the organic cage was carried out in all parts of the carrier. The active centers of the loaded palladium were also located in all parts of the carrier. Affected by the diffusion limitation of the reaction molecules, its activity selectivity was worse than that of Example 4.

[0220] In Comparative Example 5, the catalyst was prepared by a conventional method, and the activity of the catalyst was reduced because silver occupied part of the outer surface of the active center. This was similar to the situation in Comparative Example 2.

[0221] In Comparative Example 6, phenylenediamine was used instead of terphenylenediamine, and the synthesized organic cage was significantly smaller, which also made the size of the active center smaller. In the carbon dihydrogenation reaction involving CO, the activity of the catalyst was insufficient.

[0222] In Comparative Example 7, during the calcination process in step (3), the temperature is higher than the decomposition temperature of the organic cage, resulting in the disintegration of the organic cage. When palladium is loaded in step (5), part of the palladium cannot be loaded in the organic cage and can only be dispersed in other parts of the carrier, resulting in significantly low catalyst activity.

[0223] Under the condition that CO participates in the reaction, CO can be adsorbed on palladium atoms and form competitive adsorption with acetylene, which reduces the probability of forming multiple vinyl groups at the same active center at the same time, and objectively plays a role in reducing the amount of green oil generated and improving selectivity. However, CO may still form strong adsorption and undergo formylation reaction. In order to reduce the formylation reaction, it is necessary to reduce the adsorption intensity of CO on the active center. The electronic effect after silver and palladium form an alloy can be used, that is, the S electrons of silver first enter the outer empty orbit of palladium, and silver does not need to be exposed outside the active center. Silver does not occupy the position of the outer layer, so that the activity of the catalyst is not significantly reduced. Compared with the traditional method, the catalyst of the present invention has a greatly reduced loading amount of precious metal palladium, its green oil generation is also reduced, and the catalyst operation cycle is extended.

Claims

1. A catalyst for selective hydrogenation of alkynes, wherein: The active components of the catalyst contain Pd and Ag, with the mass of the carrier being 100%, the content of Pd being 0.045-0.075%, and the content of Ag being 0.06-0.12%; The catalyst contains an organic cage, which is located on the outer surface of the catalyst and has a size of 2.7-3.6 nm. The Pd is loaded in the organic cage, and Ag is located in the middle or bottom of the Pd active center.

2. The catalyst according to claim 1, wherein The specific surface area of ​​the catalyst is 15-30m 2 / g.

3. The catalyst according to claim 1 or 2, wherein The content of alumina in the carrier of the catalyst is more than 80%.

4. The catalyst according to claim 1 or 2, wherein The crystal form of the aluminum oxide in the carrier is theta, alpha or a mixed crystal form thereof; the aluminum oxide in the catalyst carrier accounts for more than 80%.

5. The catalyst according to claim 1 or 2, wherein The support further contains magnesium oxide and / or titanium oxide.

6. A method for preparing a catalyst according to any one of claims 1 to 5, comprising the following steps: (1) mixing a hydrophilic polymerizable monomer with a calcined carrier and polymerizing the mixture at a certain temperature to obtain a first semi-finished catalyst, wherein the volume of the polymer synthesized from the hydrophilic polymerizable monomer is 80-95% of the pore volume of the carrier; (2) taking tri(4-formylphenyl)amine and halogenated acetic acid and mixing them, dissolving them in alkyl halide, and then mixing them with the first semi-finished catalyst, stirring and adding dropwise a mixed solution of an aromatic diamine compound and alkyl halide, allowing the mixture to stand, and after the reaction is complete, pouring out the residual liquid, washing with alcohol and deionized water respectively, and drying to obtain a second semi-finished catalyst; The molar ratio of the aromatic diamine compound to tri(4-formylphenyl)amine is 1.2-2.5:1, and the mass ratio of tri(4-formylphenyl)amine to halogenated acetic acid is 2000-6000:1; (3) dissolving an organic palladium salt in an organic solvent to obtain a first palladium precursor solution; The second semi-finished product catalyst is immersed in an alcohol solution, the first solution of the palladium precursor is added dropwise to the mixture of the second semi-finished product catalyst and the alcohol, and stirred at the same time, and then a reducing agent is added dropwise, and heated and stirred until the surface of the second semi-finished product catalyst no longer changes color, the solution is poured off, and the product is washed with deionized water, dried, and calcined at a temperature below the decomposable temperature of the polymer formed in step (1) to obtain a third semi-finished product catalyst; (4) dissolving a soluble silver salt in deionized water or an organic solvent to obtain a silver-containing impregnation solution, immersing the third semi-finished catalyst in the silver-containing impregnation solution, allowing it to stand after it is completely absorbed, adding a reducing agent dropwise to reduce the silver, decanting the solution, washing with deionized water, and drying to obtain a fourth semi-finished catalyst; (5) dissolving an organic palladium salt in an organic solvent to obtain a second palladium precursor solution, immersing the fourth semi-finished catalyst in an alcohol solution, and dropping the second palladium precursor solution into the mixture of the fourth semi-finished catalyst and the alcohol while stirring; Add the reducing agent dropwise to the above solution, heat and stir, wait until the surface of the fourth semi-finished product catalyst no longer changes color, pour off the solution, wash and dry to obtain the catalyst, or, do not perform reduction, pour off the solution, wash with deionized water, dry, and calcine to obtain the catalyst.

7. The preparation method according to claim 6, wherein: The volume of the polymer synthesized from the hydrophilic polymerizable monomer is 85-95% of the pore volume of the carrier.

8. The preparation method according to claim 6, wherein: The mass ratio of the total mass of palladium in the organic palladium salt to tri(4-formylphenyl)amine in step (3) and step (5) is 2-14:

1.

9. The preparation method according to claim 6, wherein: In step (1), the hydrophilic polymerizable monomer is a monomer containing a carbonyl group and / or a carboxyl group and capable of undergoing polymerization or condensation reaction.

10. The preparation method according to claim 6, wherein: In step (1), the hydrophilic polymerizable monomer includes lactic acid, acrylic acid or formaldehyde.

11. The preparation method according to claim 6, wherein: In step (1), the decomposition temperature of the polymer formed by the hydrophilic polymerizable monomer is lower than 450°C.

12. The preparation method according to claim 6, wherein: In step (1), the decomposition temperature of the polymer formed by the hydrophilic polymerizable monomer is lower than 420°C.

13. The preparation method according to claim 6, wherein: In step (2), the aromatic diamine is tetraphenyl diamine or a derivative thereof having a substituent on the benzene ring.

14. The preparation method according to claim 6, wherein: In step (2), the aromatic diamine is p-quaterphenylenediamine or a derivative thereof having a substituent on the benzene ring.

15. The preparation method according to claim 14, wherein: The substituent is halogen or alkyl.

16. The preparation method according to claim 6, wherein: In step (2), the halogenated acetic acid is fluoroacetic acid or chloroacetic acid.

17. The preparation method according to claim 6, wherein: In step (2), the halogenated acetic acid is trifluoroacetic acid or dichloroacetic acid.

18. The preparation method according to claim 6, wherein: In step (2), the alkyl halide includes alkyl fluoride, alkyl chloride or alkyl bromide.

19. The preparation method according to claim 6, wherein: In step (2), the alkyl halide is methyl halide or ethyl halide.

20. The preparation method according to claim 6, wherein: In step (2), the alkyl halide is ethylene dichloride or chloroform.

21. The preparation method according to claim 6, wherein: In step (3) and step (5), the organic palladium salt includes palladium acetate or palladium acetylacetonate; When the organic palladium salt is palladium acetylacetonate, the organic solvent is chloroform; when the organic palladium salt is palladium acetate, the organic solvent is one or a combination of two or more of chloroform, dichloromethane and glacial acetic acid.

22. The preparation method according to claim 6, wherein: In step (3) and step (5), the alcohol includes ethanol or methanol.

23. The preparation method according to claim 6, wherein: In step (3), step (4) and step (5), the reducing agent is a reducing compound.

24. The preparation method according to claim 6, wherein: In step (3), step (4) and step (5), the reducing agent is one or a combination of two or more of methanol, formaldehyde, formic acid, ethanol, acetaldehyde and hydrazine hydrate.

25. The preparation method according to claim 6, wherein: In step (4), the soluble silver salt is a silver salt that is soluble in water or an organic solvent.

26. The preparation method according to claim 6, wherein: In step (4), the soluble silver salt is silver nitrate and / or silver acetylacetonate.

27. The preparation method according to claim 6, wherein: Step (4) is performed before step (3), and step (3) and step (5) are performed together.

Citation Information

Patent Citations

  • Hydrogenation catalyst and preparation method thereof

    CN101433842A

  • Selectively hydrogenating catalyst and preparation method thereof

    CN101433845A

  • Non-noble metal supported selective hydrogenation catalyst and preparation method and application thereof

    CN101664682A

  • Hydrogenation catalyst, and preparation method and application thereof in hydrogenation of p-tert-butyl phenol

    CN111203217A

  • C2 fraction alkyne selective hydrogenation catalyst

    CN112675869A